Алгоритм расчёта неравновесности термодинамических параметров в начальной точке вскипания - Кирсанов, М.В. (Геотехническая механика, 2009)
Отримано співвідношення для оцінки часу утворення мікропузирьків-зародишей при
вскіпанні води. Зроблено припущення кінетичного характеру щодо начального етапу вскіпання. Ця гіпотеза дозволяє розрахувати температурну нерівноважність між фазами, що потрібно для вибору оптимальної форми сопла гідропарової турбіни (ГПТ). Relationship for formation’s time of nuclens-microbubbles in onset of water’s boiling was derived. Kinetic hypothesis about initial point of water’s boiling was made. Temperature’s nonequilibrium between phases can calculate by this hypothesis. It is necessary for choice of the effective shape of the hydrovapour turbine’s (HVT) nozzle.